Wood properties of 17-year-old Pinus taeda L. trees under composted pulp-mill sludge fertilization by tree-ring analysis - Ortega Rodriguez, Daigard Ricardo (2018)
The analysis of the fertilization effects on wood productivity and tree-wood quality is important in forest plantations management.. The monitoring of these practices are generally defined by the continuous measurement of tree dimensions in permanent plots in periodic forest inventories. This methodology implies the availability of information restricted to a few years. On the other hand, the annual tree-ring analysis constitutes an efficient alternative methodology to the permanent plots uses. This study aimed to analyze the growth, wood density and nutritional concentration of 60 Pinus taeda trees treated with 6 different doses of composted pulp-mill sludge (CPMS): 0 , 20, 40, 80 and 100 t ha-1. Ten 17 year-old-trees for each treatment were selected, felled and wood cross sections (5 cm, thickness) were cut at the base, 1.30 m (DBH), 25, 50, 75 and 100% (6 cm, commercial trunk height). The annual tree-rings of the wood discs were delimitated and radial-longitudinally synchronized, and the tree stems reconstructed. Twin radial thin wood slices were cut transversely (DBH, trunk position), conditioned and analyzed by non-destructive techniques of X-ray densitometry and X-ray fluorescence (μ-XRF), to obtain the microdensity and wood nutrients profile. Width, density, biomass and nutrient concentration chronologies were analyzed by dendrochronological methods and correlated to seasonal variations of rainfall and temperature. Principal Component Analysis (PCA) was applied to explore the interaction of tree-ring variables, as well as analysis of variance (ANOVA) to verify the difference between treatments. The results analysis are presented in three chapters aiming to reach the main objective of this study. In Chapter I, the radial variation of the tree-ring microdensity and the integration of tree-ring density and width data in allometric equations were analyzed in order to improve the estimation of wood biomass production. Also, the response of the Pinus taeda trees to the CPMS treatments was dated. In Chapter II the response of the stem P. taeda trees development to the CPMS doses was analyzed. Increments of up to 24, 37 and 127% in the stem diameter, height and volume, respectively were observed. It is also proposed a management guide based on the simulation of P. taeda wood production under 84 t ha-1 CPMS for 21-year rotation and thinning at 7 and 13 years resulted in a wood productivity of 11.9 m3 ha-1 or 5.04 Mg ha-1 per year. In Chapter III the tree-ring nutrients concentration (phosphorus, sulfur, potassium, calcium, manganese and iron; P, S, K, Ca, Mn and Fe) were quantified. Ca and Mn decrease in the pith-bark direction; K and S decrease from the pith up to 8-9th annual tree-ring and, then, increase to the bark and Fe e P presented no distinguished radial trends. The results integration showed mainly correlations of P. taeda trees growth, wood density and nutrient concentration with local precipitation and significantly effects of CPMS soil fertilizer up to the 5th year after their application. This study provided an historical evaluation of growth, wood density and nutrient concentration of P. taeda trees. Evidencing the application of annual tree- rings in the monitoring of forest plantations under silvicultural treatments.